Plato on Women’s Natural Ability: Revisiting Republic V and Timaeus 41e3–44d2 and 86b1–92c3 - Harry, Chelsea; Ron, Polansky (Apeiron, 2016)
Abstract Despite the prominent argument for equal educational opportunity for women in Republic V, commentators frequently question Plato’s sincerity, the quality of the case made, or its significance. Undermining confidence in Plato’s advocacy of female equality are derogatory remarks about women in this and other dialogues. Since we take Plato to be sincere in the argument in Republic V, we reconcile his conclusions there about the equal educational opportunity for women with these seemingly problematic remarks by suggesting that the remarks reflect the interlocutors involved in the dialogue and conventional Athenian prejudices of that time rather than ideas that Plato held to be true. We take seriously the observation of Levin 1996, 14, “in none of those passages in which Plato makes derogatory remarks about women does he use phusis to explain why they behave in the ways of which he is critical.” Hence Plato never suggested that women were by nature limited to the position they occupied socially and politically in 5th or 4th century Athens; he understood the difference between the way they were by convention and the way that they could be, in accordance with their nature, were they to develop their natural capacities through education. We examine carefully Plato’s argument for the equal nature of women in Republic V to defend its viability. The provocation is our not finding in the extensive secondary literature a really detailed treatment of the actual argument and appreciation that it is intended as a sound philosophical argument. We then turn to the devolution schemes in Timaeus 41e–44d and 86b–92c, which again touch on the nature of women and appear to counter the position we attribute to Plato, to show that they are really supportive of our account. Both the Republic and Timaeus limit the natural differences between males and females to body-type. Therefore, even relative physical weakness of women’s bodies does not much problematize for Plato that their natural abilities are equal to those of men, where nature in these contexts means suitability to perform certain functions.
Keywords: dept.phi

The task of justice - Pettigrew, D. (Pathways to Reconciliation: Between Theory and Practice, 2016)
Contemporary discourse about human rights makes pragmatic use of the 1948 United Nations Universal Declaration on Human Rights, as the Declaration presents a set of guidelines that are based on assumptions about the nature of human beings: Their thoughts, ideas, freedom of expression and freedom of association.1 Article 1 of the Declaration states, for example, that ‘All human beings are born free and equal in dignity and rights. They are endowed with reason and conscience and should act towards one another in a spirit of brotherhood.’ The document engages the idea of the human being as having rights, regardless of ethnicity or gender. Such rights include life, protection from harm, and access to the latest in scientific technology.2 © Philipa Rothfield, Cleo Fleming and Paul A. Komesaroff 2008.
Journal Abbreviation: Pathways to Reconciliation: Between Theory and Practice
Keywords: dept.phi

Virtues, vices, and situations: What warrants the ascription of character traits - Yang, X. (Journal of Theoretical and Philosophical Psychology, 2016)
In recent years, situationism in psychology has caught the attention of philosophers. Some have defended it. Some have argued against it. The situationist has challenged the traditional view shared by personality psychology and virtue ethics that people differ in terms of character or character traits and that we can explain and predict people's behavior by character traits people have. Previous responses to situationism try to show that experiments from social psychology do not undermine the traditional view. I agree and will further argue that the fact that experiments do not undermine the traditional view is not sufficient to warrant the attribution of character traits, and that some philosophical arguments are needed given that not enough empirical data that show a high degree of behavioral consistencies are available. I first offer an account of the ordinary attribution of character traits according to which having character traits is a matter of degree, and argue that the ordinary attribution account comes from the Aristotelian moral psychology and is consistent with a long-standing tradition, the trait paradigm, in personality psychology. Second, I argue that although situational factors play some role in explaining and predicting behavior, the attribution of character traits plays a primary and indispensable role. Third, I argue that ordinary attribution of character traits has important functions in our moral life, which cannot be fulfilled by the attribution of local traits suggested by the situationist. I also argue that the ethical management of situations recommended by the situationist can help in getting things right, but is not sufficient to be the adequate foundation for our normative discourse. © 2016 American Psychological Association.
2 citations (Crossref) [2023-10-31]
Keywords: Attribution of character traits; Crosssituational consistency and variation; Local traits; Situationism; Virtues; dept.phi